Mini Nutritional Assessment Short‐Form predicts exacerbation frequency in patients with chronic obstructive pulmonary disease. Issue 8 (10th September 2014) - Yoshikawa, Masanori; Fujita, Yukio; Yamamoto, Yoshifumi; Yamauchi, Motoo; Tomoda, Koichi; Koyama, Noriko; Kimura, Hiroshi
Abstract Background and objective Exacerbations of chronic obstructive pulmonary disease (COPD) are a major cause of morbidity, mortality and reduced health status. Thus, to predict and prevent exacerbations is essential for the management of COPD. The aims of this study were to determine whether nutritional status as assessed by the Mini Nutritional Assessment Short‐Form (MNA‐SF) predicts COPD exacerbation and to compare the ability of the MNA‐SF to predict COPD exacerbation with that of the COPD Assessment Test (CAT). Methods Pulmonary function, the modified Medical Research Council (mMRC) scale and body mass index (BMI) were evaluated in 60 stable patients with COPD (mean age, 72 years; mean forced expiratory volume in 1 s (FEV1), 51.1% predicted). The MNA‐SF and CAT were also completed. Exacerbations were recorded prospectively for 1 year after the initial assessment. Results The mean MNA‐SF score was 11.4 ± 2.4 (well nourished, 51%; at risk, 37%; and malnourished, 12%). The mean CAT score was 14.4 ± 7.5 (low impact, 37%; medium impact, 38%; high impact, 20%; and very high impact, 5%). The CAT scores were significantly associated with the mMRC scale and %FEV1, but were not associated with BMI and the MNA‐SF score. The exacerbation frequency was associated with the MNA‐SF score but not with the CAT score. Conclusions The MNA‐SF predicts COPD exacerbation independently of the CAT.